2012
DOI: 10.1111/j.1365-2559.2012.04217.x
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and laryngeal carcinoma prognosis: nuclear localization and expression of splice variants

Abstract: Nuclear expression of survivin appears to influence LSCC aggressiveness, a higher nuclear survivin expression correlating with a higher recurrence rate and a shorter DFS. Wild-type survivin was the most frequently detected splice variant in LSCC tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
4
14
1
Order By: Relevance
“…Several previous studies have described survivin expression in laryngeal carcinoma, but contradictory results have been reported. In our series, survivin nuclear reaction predominated, in agreement with several previous studies [27,28,33]. Meanwhile, other researchers found that survivin was mainly distributed in LSCC cytoplasm [23,38].…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies have described survivin expression in laryngeal carcinoma, but contradictory results have been reported. In our series, survivin nuclear reaction predominated, in agreement with several previous studies [27,28,33]. Meanwhile, other researchers found that survivin was mainly distributed in LSCC cytoplasm [23,38].…”
Section: Discussionsupporting
confidence: 93%
“…Literature data suggests higher expression of survivin (nuclear or cytoplasmic or both), as an apoptotic marker which correlates significantly with tumor grade, stage, and patient outcome including recurrence rate, and disease-free survival rate [12,[36][37][38]. Current reports in these research areas are inconsistent and propose opposing conclusions regarding the significance and prognostic value of nuclear and cytoplasmic immunoexpression of survivin [30].…”
Section: Discussionmentioning
confidence: 81%
“…The six known splice variants of the survivin gene transcript have recently been found to localise in different subcellular components, where they have distinct functions 1 2. Survivin is transiently expressed during embryonic development, then barely detectable in normal, differentiated adult cells and tissues, apart from certain tissues such as the thymus and placenta 2.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of laryngeal squamous cell carcinoma (LSCC), the nuclear expression of survivin appears to influence the tumour's aggressiveness, and wild-type survivin is the most frequently detected splice variant 1. The novel main aim of this study was to conduct a preliminary investigation into the possible role of survivin expression in LSCC neoangiogenesis, as determined from endoglin-assessed MVD.…”
Section: Introductionmentioning
confidence: 99%